2021
DOI: 10.1155/2021/6692568
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Privacy‐Preserving Authentication Protocol Using Bilinear Pairings for the VANET Environment

Abstract: With the rapid development of communication and microelectronic technology, the vehicular ad hoc network (VANET) has received extensive attention. However, due to the open nature of wireless communication links, it will cause VANET to generate many network security issues such as data leakage, network hijacking, and eavesdropping. To solve the above problem, this paper proposes a new authentication protocol which uses bilinear pairings and temporary pseudonyms. The proposed authentication protocol can realize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The proposed system follows a similar security threat model as mentioned in [28] and [4]. At first, all the entities in our system are separated into one of the following two categories.…”
Section: A Threat Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The proposed system follows a similar security threat model as mentioned in [28] and [4]. At first, all the entities in our system are separated into one of the following two categories.…”
Section: A Threat Modelmentioning
confidence: 99%
“…Moreover, any other entity that is not registered and external to the system is referred to as an unauthorized entity. Based on curious, semi-trusted, and unauthorized entities to the system, we now categorize the potential threat into internal and external adversaries as also mentioned in [4] by Zhang et al…”
Section: A Threat Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…To prevent RSU capture attacks and OBU intrusion assaults, they employed physical unclonable function and biological keys, and we devise a advantage embedding technique with dynamic pseudonym-ID to allow the TA to restore the identity of a compromised vehicle. Zhang et al [10] suggested a novel authentication mechanism based on bilinear pairings and short-lived pseudonyms, which the suggested authentication protocol can include features like authenticating the vehicle's identification and validating its sent messages. In order to solve the escrow issue and make certificates unnecessary, Imghoure et al [11] proposed an authentication with a privacy system that uses elliptic curve cryptography (ECC) instead of the more conventional Map-to-Hash function and bilinear pairing.…”
Section: Related Workmentioning
confidence: 99%